Phytochemical profile of Brazilian grapes (Vitis labrusca and hybrids) grown on different rootstocks - da Silva, Marlon Jocimar Rodrigues; Paiva, Ana Paula Maia [UNESP]; de Souza, Joyce Fagundes; da Silva Padilha, Carla Valéria; Basílio, Letícia Silva Pereira [UNESP]; dos Santos Lima, Marcos; Pereira, Giuliano Elias; Corrêa, Luiz Claudio; Vianello, Fabio; Lima, Giuseppina Pace Pereira [UNESP]; Moura, Mara Fernandes; Tecchio, Marco Antonio [UNESP] (Public Library of Science (PLoS), 2022)
Important factors may influence the bioactive compounds in grapes, including scion–rootstock interaction. Therefore, the bioactive compounds and antioxidant activity in grape skin and pulp fractions of ‘Isabel Precoce’, ‘BRS Carmem’, ‘BRS Cora’, ‘BRS Violeta’ and ‘IAC 138–22 Máximo’ were assessed. These cultivars, from genetic improvement programs in Brazil, have good adaptation to subtropical and tropical climate conditions, and can be widely used by winegrowers aiming at adding value to the grape. All grapevines were grafted onto ‘IAC 766’ and ‘IAC 572’ rootstocks under tropical conditions in Brazil. The highest concentration of bioactive compounds was found in skins of ‘BRS Violeta’, followed by ‘IAC 138–22 Máximo’, both grafted onto ‘IAC 766’. There was a strong correlation between phenolic content and antioxidant properties, since antioxidant activity also decreased in the sequence: ‘BRS Violeta’ > ‘IAC 138–22 Máximo’ > ‘BRS Cora’ > ‘BRS Carmem’ > ‘Isabel Precoce’. Skin from hybrid grapes (‘BRS Violeta’, ‘IAC 138–22 Máximo’, ‘BRS Cora’ and ‘BRS Carmem’) grafted in both rootstocks contains higher levels of (poly)phenolic compounds and antioxidant activity than ‘Isabel Precoce’ (V. labrusca). Skin from ‘BRS Violeta’ grafted onto’IAC 766’ stand out from the others due to their high content of bioactive compounds.